Implantação de um programa de envolvimento do trabalhador inspirado no Kaizen: China vis à vis ao Brasil - Domingues, Larissa Cecília (2017)
Since the 1980s, after a series of publications in the academic and business literature, initiatives to implement the Toyotist approach become common in companies located in developed countries and, consequently, in organizations located in Latin America, Asia and Africa, as the headquarters begin to spread their learning to their subsidiaries. Thus, this work aimed to study the multi-plant adoption of a kaizen-based employee involvement program in two branches of an organization, located in Brazil (BR) and China (CH). Among the various programs and techniques associated with Lean Manufacturing, the choice for kaizen was due to the interest in understanding the possible mismatches between the discourses present in the Toyotist literature and the reality of modern companies that call themselves lean. The analysis of the results allowed to understand the main differences between BR and CH programs, with emphasis on the level of employee participation, the use of group ideas, the rewards system and the gains obtained. It should be noted that in BR the level of employee adherence to the program has been greater and this fact can be explained in part by its alignment with critical managerial practices to the establishment of the environment and model conducive to the culture of continuous improvement. However, the research found that the organization has failed in 9 of the 18 practices evaluated for BR and in 13 of the 18 practices evaluated for CH. That is, although the Toyotist literature presents kaizen programs as a form of partnership, collaboration and sharing between employee and employer, this becomes subject oof questions in the context studied.